2021
DOI: 10.3390/biom11091295
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Reverses NNMT-Induced 5-Fluorouracil Resistance via Increasing ROS and Cell Cycle Arrest in Colorectal Cancer Cells

Abstract: Nicotinamide N-methyltransferase (NNMT) plays multiple roles in improving the aggressiveness of colorectal cancer (CRC) and enhancing resistance to 5-Fluorouracil (5-FU), making it an attractive therapeutic target. Curcumin (Cur) is a promising natural compound, exhibiting multiple antitumor effects and potentiating the effect of 5-FU. The aim of the present study is to explore the effect of Cur on attenuating NNMT-induced resistance to 5-FU in CRC. A panel of CRC cell lines with different NNMT expressions are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 42 publications
1
34
0
Order By: Relevance
“…ROS are cellular signaling proteins that are involved in every phase of cellular metabolism (Ye et al., 2021b ). Cur can increase the production of ROS, leading to many dysfunctions in cells, including DNA damage, apoptosis, and cell cycle arrest in cancer cells (Li et al., 2021 ). To verify the mechanism of inducing apoptosis, ROS production in cancer cells was detected by a ROS probe.…”
Section: Resultsmentioning
confidence: 99%
“…ROS are cellular signaling proteins that are involved in every phase of cellular metabolism (Ye et al., 2021b ). Cur can increase the production of ROS, leading to many dysfunctions in cells, including DNA damage, apoptosis, and cell cycle arrest in cancer cells (Li et al., 2021 ). To verify the mechanism of inducing apoptosis, ROS production in cancer cells was detected by a ROS probe.…”
Section: Resultsmentioning
confidence: 99%
“…Results showed that the m 6 A demethylase FTO was positively associated Overall survival with CPEB1 in both colon and stomach adenocarcinoma (Figure 5A). Knockdown of FTO significantly decreased the expression of CPEB1 (Figure 5B), which suggested that m 6 A modification could be involved in the increase levels of CPEB1 in colon and stomach adenocarcinoma cells. In subsequent study, a RIP assay validated m 6 A modification of CPEB1 mRNA in colon and stomach adenocarcinoma cells and also confirmed the role played by FTO in this modification (Figure 5C).…”
Section: Fto-induced M 6 a Modification Is Responsible For Increasing...mentioning
confidence: 88%
“…Knockdown of FTO significantly decreased the expression of CPEB1 (Figure 5B), which suggested that m 6 A modification could be involved in the increase levels of CPEB1 in colon and stomach adenocarcinoma cells. In subsequent study, a RIP assay validated m 6 A modification of CPEB1 mRNA in colon and stomach adenocarcinoma cells and also confirmed the role played by FTO in this modification (Figure 5C). As shown in Figure 5D, the expression levels of FTO and CPEB1 were increased in tumor tissues compared to their adjacent normal tissues (Figure 5D,5E).…”
Section: Fto-induced M 6 a Modification Is Responsible For Increasing...mentioning
confidence: 88%
See 2 more Smart Citations